Nature Inspired Computing Techniques for Optimal Reactive Power Dispatch - Rebecca Ng, Shin Mei; Mohd Herwan, Sulaiman; Zuriani, Mustaffa; Hamdan, Daniyal (Universiti Malaysia Pahang, 2016)
This paper presents the application of recent nature inspired computing techniques namely gray wolf optimizer (GWO) and ant lion optimizer (ALO) in solving optimal reactive power dispatch (ORPD) problem. GWO and ALO are utilized to minimize the transmission losses by finding the best combination of control variables such as generator voltages, transformer tap ratios as well as reactive compensation devices. In this paper, IEEE 30-bus system is utilized to show these techniques in solving ORPD. The comparison between the effectiveness of GWO and ALO are made and reported in this paper. The results show that GWO is able to gain a better result in solving ORPD than ALO.